Metamemory as evidence of animal consciousness: the type that does the trick. - Shea, N; Heyes, C (Springer Netherlands, 2010)
The question of whether non-human animals are conscious is of fundamental importance. There are already good reasons to think that many are, based on evolutionary continuity and other considerations. However, the hypothesis is notoriously resistant to direct empirical test. Numerous studies have shown behaviour in animals analogous to consciously-produced human behaviour. Fewer probe whether the same mechanisms are in use. One promising line of evidence about consciousness in other animals derives from experiments on metamemory. A study by Hampton (Proc Natl Acad Sci USA 98(9):5359-5362, 2001) suggests that at least one rhesus macaque can use metamemory to predict whether it would itself succeed on a delayed matching-to-sample task. Since it is not plausible that mere meta-representation requires consciousness, Hampton's study invites an important question: what kind of metamemory is good evidence for consciousness? This paper argues that if it were found that an animal had a memory trace which allowed it to use information about a past perceptual stimulus to inform a range of different behaviours, that would indeed be good evidence that the animal was conscious. That functional characterisation can be tested by investigating whether successful performance on one metamemory task transfers to a range of new tasks. The paper goes on to argue that thinking about animal consciousness in this way helps in formulating a more precise functional characterisation of the mechanisms of conscious awareness.